The age of beloveds: love and the beloved in early-modern Ottoman and European culture and society - Andrews, Walter G. (Duke Univ. Press, 2006)
Introduction -- Beloved boys (and girls) -- Love scripts I, male bonding -- Love scripts II, poems about poetry about love -- Love, sex, and poetry -- Women and the art of love -- Seduction and reversal -- To die for . . . : love and violence in the age of beloveds -- Love, law, and religion -- The end of an age -- Renaissance, renaissances, and the age of beloveds -- Appendix : Ottoman sultans during the age of beloveds